An Analysis Of Educational Values In “Keluarga Cemara” Movie - Nurdini, Rahmi Aulia; Apriyanti, Fitri (JUPE : Jurnal Pendidikan Mandala, 2023)
Finding the positive effects and educational values of watching movies for study was one of the study's main objectives. "Keluarga Cemara" is the title of the movie that was utilized for this study. The method of analysis used in this study is qualitative descriptive. For this thesis, data from two sources were employed. The primary data source came from the movie in the form of dialogue scripts between every character. The second set of data was gathered from research-related journals and other online resources. Descriptive qualitative research was used in this film. According to the analysis, it was noticed that a number of educational values had been found, including: honestly, brave, peace, confident & potential, self-discipline moderation, purity, loyalty, respect, love & affection, not selfishness, kind & friendly, and fair & humanist. Additionally, watching "Keluarga Cemara" offered both the the benefits of both as an educational tool and a relaxing leisure activity.